Ameliorating Effect of Fermented Perilla frutescens on Sleep Deprivation-Induced Cognitive Impairment Through Antioxidant and BDNF Signaling in Mice - Seo, Chae Ryeong; Lee, Bo Kyung; Jee, Hye Jin; Yoo, Jae Ryeong; Lee, Chul Kyu; Park, Jin Wook; Jung, Yi Sook (Nutrients, 2024)
Background: Adequate sleep is essential for maintaining cognitive function, as evidenced by literature. Perilla frutescens var. acuta Kudo (PF) is a traditional medicinal herb reported to improve vascular cognitive impairment and induce sedation. However, the effects of PF on cognitive impairment caused by sleep deprivation (SD) have not yet been evaluated. This study aims to evaluate the effects of fermented PF (FPF) and its underlying mechanisms in a model of SD-induced cognitive impairment. Methods: Mice were subjected to SD to establish cognitive impairment, and FPF was administered once daily for 3 days. Cognitive performance was assessed using Y-maze and passive avoidance tests, followed by molecular mechanisms analyses. Results: FPF treatment improved SD-induced cognitive impairment, as evidenced by increased spontaneous alternation and extended latency time. Histological analysis revealed that SD impaired the hippocampus, and this impairment was alleviated by FPF treatment. FPF demonstrated antioxidant activity by increasing glutathione levels and decreasing malondialdehyde levels. Furthermore, the decreased levels of brain-derived neurotrophic factor (BDNF) observed in sleep-deprived mice were restored with FPF treatment. FPF also enhanced the phosphorylation of tropomyosin receptor kinase B, extracellular signal-regulated kinase, and cAMP response element-binding protein. Conclusions: These results indicate that FPF may have beneficial effects on SD-induced cognitive impairment by protecting against oxidative stress and increasing BDNF expression.
Keywords: Animals; Antioxidants; Brain-Derived Neurotrophic Factor; Cognitive Dysfunction; Cyclic AMP Response Element-Binding Protein; Disease Models, Animal; Fermentation; Glutathione; Hippocampus; Male; Maze Learning; Mice; Oxidative Stress; Perilla frutescens; Plant Extracts; Receptor, trkB; Signal Transduction; Sleep Deprivation; brain-derived neurotrophic factor; cognitive impairment; fermentation; oxidative stress; Perilla frutescens; sleep-deprivation